Student Retention/Attrition. - Polka, Joseph (1998)
Keywords: dept.soc; faculty_collection; sabbatical_report

New Spirituality, Self, and Belonging: How New Agers and Neo-Pagans Talk About Themselves - Bloch, Jon P. (Praeger, 1998)
Keywords: Case studies; Neopagans; Case studies; New Age movement; Interviews; Interviews; Neopagans; New Age persons; Psychology; Social aspects; Neopaganism; Social aspects; New Age persons; dept.soc; faculty_collection

Alternative spirituality and environmentalism - Bloch, JP (Review of Religious Research, 1998)
The relationship between religiosity and environmentalism has previously been examined by studying conservative versus liberal Christian affiliation. This study explores environmentalist attitudes amongst persons whose religiosity does not fit conventional patterns: the so-called “alternative” or “countercultural” spiritual community (e.g, New Age, Neo-Paganism). This network of individuals finds commonalty and solidarity not through organizational ties or a singular theology, but through an overriding ideology that challenges the alleged rigidity and dualistic dogma of mainstream society, and so suggests a new form of social movement. Central to this critique of the mainstream is the notion that the earth is just as sacred as the “heavens,” and so by preserving the earth, one is being “spiritual. “ Excerpts from in-depth interviews with 22 alternative spiritualists feature numerous key environmental/spiritual themes. These excerpts indicate that issues such as religiosity, “liberal” versus “conservative” affiliation, and environmental politics can take on different meanings when explored outside of mainline Christianity.
16 citations (Crossref) [2023-10-31] tex.unique-id: ISI:000075547900004
Keywords: dept.soc